2022
DOI: 10.3390/children9071047
|View full text |Cite
|
Sign up to set email alerts
|

Lung Abscess Case Series and Review of the Literature

Abstract: (1) Background: Lung abscess is a lung infection that leads to the destruction of the lung parenchyma, resulting in a cavity formation and central necrosis filled with purulent fluids. It is an uncommon pediatric problem, and there is a paucity of literature reviews on this subject, especially for the pediatric age group. Lung abscess is commonly divided into those considered primary in previously well children or secondary in those with predisposing co-morbidities. The predominant pathogens isolated from prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
14

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 14 publications
(24 reference statements)
0
4
0
14
Order By: Relevance
“…EES lacks distinct clinical manifestations, often leading to diagnostic and therapeutic management delays 16. As in our case, the patient presented with symptoms of localised chest pain, dyspnoea, cough and low-grade fever, commonly observed in other clinical scenarios such as pneumonia or lung abscess.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…EES lacks distinct clinical manifestations, often leading to diagnostic and therapeutic management delays 16. As in our case, the patient presented with symptoms of localised chest pain, dyspnoea, cough and low-grade fever, commonly observed in other clinical scenarios such as pneumonia or lung abscess.…”
Section: Discussionmentioning
confidence: 50%
“…As in our case, the patient presented with symptoms of localised chest pain, dyspnoea, cough and low-grade fever, commonly observed in other clinical scenarios such as pneumonia or lung abscess. Accordingly, antibiotics were prescribed, providing temporary relief, and serological–culture tests were done, which came out to be sterile 16…”
Section: Discussionmentioning
confidence: 99%
“…Since patient characteristics and risk factors for LA, as well as prevalence of microorganisms, differs across clinical settings and countries, there is also a need for larger observational studies that could help identify risk factors for developing LA and improve our clinical understanding of this complex infection. In children, a recent review also concluded that the evidence about LA is sparse [27 ▪ ]. The authors of this review also state that there is unwarranted variation in the clinical management.…”
Section: Discussionmentioning
confidence: 89%
“…A recent review [27 ▪ ] found that the clinical manifestation of LA in children is comparable to that seen in adults, with variations in symptomatology, site of infection, microorganism, among others.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…sedangkan abses paru sekunder dapat disebabkan oleh bakteri anaerob (27%), Pseudomonas aeruginosa, (13%) Staphylococcus aureus (13%), Streptococcus pneumonia (7%), Haemophilus influenza (7%), dan Escherichia coli, atau klebsiella. [6][7][8] Diagnosis dan tatalaksana abses paru pada anak didasarkan pada menifestasi klinis yang terjadi. Diagnosis diperkuat dengan rontgen dada, ultrasonografi, dan computed tomography (CT Scan).…”
unclassified